Impact of conventional banking financing and Islamic banking financing on economic growth 2008-2018 - Hasymi Nur Baehaqy; Eko Fajar Cahyono (Universitas Airlangga, 2019)
This research aims to know Impact of conventional banking financing and Islamic banking financing on economic growth 2008-2018. In this study the authors used a saturated sampling technique found in Non-Probability Sampling. The analysis technique used is VECM (Vector Error Correction Model). Based on the results of the study indicate that there is a one-way relationship on several variables, namely Conventional Banking Financing to GDP and Conventional Banking Financing to Islamic Banking Financing, In the long run, Conventional Banking Financing has a positive and significant relationship to GDP, whereas Islamic Banking Financing has a negative and significant relationship to GDP.Keywords: Banking Financing, Economic Growth, GDP (Gross Domestic Product), VECM (Vector Error Correction Model)REFFERENCESAam, Slamet Rusydiana. 2009. Hubungan Antara Perdagangan Internasional, Pertumbuhan Ekonomi Dan Perkembangan Industri Keuangan Syariah Di Indonesia. Jurnal Islamic Finance & Business Review, Vol.4, 1, (2009),h.53.Abdul Ghofur Anshori. 2009. Perbankan Syariah di Indonesia. Yogyakarta: Gadjah Mada University Press.Abduh, Muhamad dan Mohd Azmi Omar. 2012. Islamic Banking and Economic Growth: the Indonesian Experience. International Journal of Islamic and Middle Eastern Finance and Management, Vol. 5, No. 1.Abu, Mujahid. 2007. Kewajiban Bekerja. Media Dakwah Islam.Net, 2007A. McEachern, William. 2000. Ekonomi Makro: Pendekatan Kontemporer. Jakarta: Salemba Empat.Arifin, Imamul, Hadi, W, Giana. 2009. Membuka Cakrawala Ekonomi. Bandung: Grafindo.Andiwarman, Karim. 2004. Bank Islam Analisis Fiqih dan Keuanagan. Jakarta: PT Raja Grafindo Persada.Andrian Tony Prakoso. 2009. Analisis Hubungan Perdagangan Internasionaldan FDI Terhadap Pertumbuhan Ekonomi Indonesia”, (Skripsi S1 Universitas Indonesia, 2009), h.65.Antonio, muhammad Syafi’i. 2001. Bank Syariah Dari Teori ke Praktik. Jakarta: Gema Insani Press. Arcand, Jean-Louis., Enrico Berkes, dan Ugo Panizza. 2012. Too Much Finance?IMF Working Paper, WP/12/161.Ascarya. 2006. Akad dan Produk Bank Syariah : Konsep dan Praktek diBeberapa Negara. Jakarta: Bank Indonesia Ascarya. 2012. Alur Transmisi dan Efektifitas Kebijakan Moneter Ganda diIndonesia. Buletin Ekonomi Moneter dan Perbankan Januari.Badan Pusat Statistik. 2008-2018. Produk Domestik Bruto. Badan Pusat Statistik (Statistik Indonesia), Jakarta.Baily, Martin Neil, Robert J. Gordon, dan Robert M. Solow . 1981. Productivityand the Services of Capital and Labor. Brookings Papers on EconomicActivity Vol. 1981, No.1, pp. 1-65.Bappenas. 2017. Perkembangan Ekonomi Indonesia dan Dunia Triwulan I Tahun 2017. Jakarta: Bappenas.Barro, R.J. 1999. Economic Growth in Cross-secction of Countries. Quarterly Journal of Economics, 106, pp. 407-444.Boediono. 1981. Teori Pertumbuhan Ekonomi. Yogyakarta: BPFE UGMChow, Gregory C. dan Kui-Wai Li. 2002. China’s Economic Growth : 1952-2010. Economic Development and Cultural Change, Vol. 51, No. 1, pp.247-256. The University of Chicago Press.Consuelo G. Sevilla, dkk. 2006. Pengantar Metode Penelitian. Jakarta: UI-Pres, h.71.Damodar N. Gujarati. 2006. Dasar-dasar Ekonometrika Jilid 2. PT. Gelora Aksara Pratama. h.166.Dina, Acyuninda dan Umanto Eko P. 2013. Analisis Hubungan Antara Inflasi Dan Pertumbuhan Ekonomi Di Indonesia MenggunakanPendekatanKointegrasi Dan Kausalitas Granger Pada Periode 2000-2012 “ (Ilmu Administrasi Niaga, Fakultas Ilmu Sosial dan Ilmu Politik, Fisip UI, 2013), h.12.Dumairy. 2015. Bank Islam, Materi Kuliah Sistem dan Lembaga KeuanganSyariah FEB UGM, tidak diterbitkan.Dumairy. 2015. Pilar Sistem Keuangan Islam. Materi Kuliah Sistem danLembaga Keuangan Syariah FEB UGM, tidak diterbitkan.Gambacorta, Leonardo, Jing Yang, dan Kostas Tsatsaronis. 2014. Financial Structure and Growth . BIS Quarterly Review March 2014.Gujarati, Damodar N. 2003. Basic Econometrics, Fifth Edition. New York:McGraw-Hill Irwin. Hasin, Zamrah dan M. Shabri Abd Majid. 2011. The Importance of IslamicBanks in the Monetary Transmission Mechanism in Malaysia.InternationalConference on Idlamic Economics and Finance 8th.Inggrid. 2006. Sektor Keuangan dan Pertumbuhan Ekonomi di Indonesia: Pendekatan Kausalitas dalam Multivariate Vector Error Correction Model (VECM). Jurnal Manajemen dan Kewirausahaan Fakultas Ekonomi UK Petra, 8:40-50.Iskandar dan Sugiharso Safuan. 2010. Analisis Hubungan Perkembangan SektorKeuangan dan Pertumbuhan Ekonomi di Indonesia (PendektanAutoregressive Distributed Lag.Ismail. 2010. Manajemen Perbankan. Surabaya: Kencana.Johnson. 2015. Analysis of the impact of the economic credits on the inflationand economic growth in Togo. African Journal of Marketing Managementvol 7 pp 68-79, July 2015.Kasmir. 2002. Bank dan Lembaga Keuangan Lainnya. Edisi Revisi 2002.Jakarta: PT. Rajagrafindo PersadaKing, Robert G. and Ross Levine. 1993. Finance and Growth, Schumpeter Mightbe Right. The Quarterly Journal of Economics, Vol 108, No.3, pp. 717-737.Oxford University Press.Kurniasari, Widita. 2010. Analisis Pengaruh Kredit Perbankan dan TenagaKerja terhadap Pertumbuhan Ekonomi Indonesia. Unpublished MasterDissertation, Universitas Indonesia, Depok.Kuncoro, Mudrajad.2009. Metode Riset Untuk Bisnis & Ekonomi. Jakarta:Erlangga. Levine, Ross dan Sara Zervos. 1998. Stock Markets, Banks, and EconomicGrowth. The American Economic Review, Vol 88 No.3, pp. 537-558.Lewis, Mervyn dan Latifa Algaoud. 2001. Islamic Banking. Diterjemahkan oleh Burhan Wirasubrata. Jakarta: PT Serambi Ilmu Semesta Anggota IKAPI.Maia, Alexandre Gori dan Esther Menezes. 2014. Economic Growth, Labor andproductivity in Brazil and the United States : a comparative analysis.Revista de Economica Politica June 2014.Mankiw, N. Gregory. 2003. Macroeconomics. Seventh Edition. New York :Worth Publisher.Moh. Toekam. 1999. Perkreditan Bisnis Inti Bank Komersial. Jakarta: PT. Gramedia.Otoritas Jasa Keuangan. 2008-2018. Statistik Perbankan Indonesia. Jakarta: Otoritas Jasa Keuangan.Otoritas Jasa Keuangan. 2008-2018. Statistik Perbankan Syariah. Jakarta: Otoritas Jasa Keuangan.Rahmi Rahmawati. 2016. Pengaruh Faktor Makroekonomi Terhadap Kinerja Keuangan Perbankan Syariah di Indonesia. (Skripsi S1 Fakultas Syariah dan Hukum Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2016), h.63Ribut Wahyudi. 2009. Analisis Vector Auto Regressive (VAR) Transaksi Instrumen Moneter Syariah Terhadap Kinerja Perbankan Syariah di Indonesia. (Skripsi S1 Fakultas Ekonomi dan Bisnis UIN Syarif Hidyatullah Jakarta, 2009), h. 45.Ris, Yuwono Yudo Nugroho. 2009. Analisis Faktor-faktor Penentu Pembiayaan Perbankan Syariah di Indonesia : Aplikasi Model Vector Error Correction”,(Tesis. Institut Pertanian Bogor, 2009), h.77-79.Rivai, Veithzal dkk. 2007. Bank and Financial Institution Management: Conventional and Sharia System, Jakarta: PT Raja Grafindo Persada.Said Sa’ad Marthon. 2004. Ekonomi Islam Ditengah Krisis Ekonomi Global. Jakarta: Zikrul Hakim, hlm. 142.Sukirno, Sadono. 2002. Makroekonomi Modern. Jakarta: PT Raja Drafindo PersadaSuseno dan Piter Abdullah. 2003. Sistem dan Kebijakan Perbankan di Indonesia.Seri Kebanksentralan no. 7. Jakarta: Bank Indonesia.Sukirno, Sadono. 2004. Pengantar Teori Makroekonomi. Jakarta: PT RajaGrafindo Persada.Undang-undang Perbankan Syariah. 2008. ——————-.Jakarta: Sinar Grafika. Undang-undang Perbankan. 2009. ———————.Jakarta: Sinar Grafika.